2011
DOI: 10.1088/0004-637x/742/2/68
|View full text |Cite
|
Sign up to set email alerts
|

The Host Galaxies of Low-Mass Black Holes

Abstract: Using Hubble Space Telescope observations of 147 host galaxies of low-mass black holes (BHs), we systematically study the structures and scaling relations of these active galaxies. Our sample is selected to have central BHs with virial masses of ∼10 5 -10 6 M . The host galaxies have total I-band magnitudes of −23.2 < M I < −18.8 mag and bulge magnitudes of −22.9 < M I < −16.1 mag. Detailed bulge-disk-bar decompositions with GALFIT show that 93% of the galaxies have extended disks, 39% have bars, and 5% have n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
150
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(172 citation statements)
references
References 118 publications
(222 reference statements)
20
150
1
Order By: Relevance
“…10). However, this is not the case for the M BH −M bulge relation: the BH mass of IMBHs/low-mass AGN tends to be lower at a given bulge mass than expected from an extrapolation of the relation found for classical bulges (e.g., Greene et al 2008;Jiang et al 2011;Graham & Scott 2013Baldassare et al 2015Baldassare et al , 2017Nguyen et al 2017). SMBHs in inactive galaxies with pseudobulges (Hu 2008;Kormendy & Ho 2013) and spiral galaxies with megamaser BH mass measurements (Greene et al 2010;Läsker et al 2016) are also found to fall below the M BH − M bulge relation of early-type galaxies (Kormendy & Ho 2013), which suggests that most IMBHs/low-mass AGN are hosted by late-type galaxies (Greene & Ho 2007a;Ho & Kim 2016).…”
Section: X-ray Weak Imbhs: Hiding Behind the Dust?mentioning
confidence: 91%
“…10). However, this is not the case for the M BH −M bulge relation: the BH mass of IMBHs/low-mass AGN tends to be lower at a given bulge mass than expected from an extrapolation of the relation found for classical bulges (e.g., Greene et al 2008;Jiang et al 2011;Graham & Scott 2013Baldassare et al 2015Baldassare et al , 2017Nguyen et al 2017). SMBHs in inactive galaxies with pseudobulges (Hu 2008;Kormendy & Ho 2013) and spiral galaxies with megamaser BH mass measurements (Greene et al 2010;Läsker et al 2016) are also found to fall below the M BH − M bulge relation of early-type galaxies (Kormendy & Ho 2013), which suggests that most IMBHs/low-mass AGN are hosted by late-type galaxies (Greene & Ho 2007a;Ho & Kim 2016).…”
Section: X-ray Weak Imbhs: Hiding Behind the Dust?mentioning
confidence: 91%
“…If one was to separate the galaxies in Figure 2 at M bh = 2×10 6 M ⊙ , one would (understandably but inappropriately) conclude that the lower mass spheroids do not follow an M bh -M sph, * relation (Jiang et al 2011). Busch et al 2014) are denoted by the cross hairs.…”
Section: A Bend In the Roadmentioning
confidence: 99%
“…We estimate virial BH masses using the formalism for singleepoch spectra, recently recalibrated for the Hβ line by Ho & Kim (2015), which takes into consideration the dependence of the virial coefficient (so-called f -factor) on bulge type (Ho & Kim 2014), as well as the latest updates to the M BH − σ * relation of inactive galaxies (Kormendy & Ho 2013), on which the calibration of the f -factor is based. As our sample specifically targets low-mass BHs, we expect, from experience with other similar samples Jiang et al 2011b), that the host galaxies contain pseudobulges. The BH mass estimator of Ho & Kim (2015) is based on the FWHM of broad Hβ and the AGN continuum luminosity at 5100 Å, whereas the primary measurements in this study come from the FWHM and luminosity of broad Hα.…”
Section: Broad Hα Black Hole Masses and Eddington Ratiosmentioning
confidence: 99%